Transition for adolescents with learning disabilities and an immunodeficiency - Alderson, Eliška; Lally, Sarah; Campbell, Mari (Frontiers in Immunology, 2023)
Many adolescents with immunodeficiency are diagnosed with a comorbid learning disability. The process of transition from paediatric to adult healthcare for these individuals occurs with a range of additional challenges. Due to the lack research available on immunodeficiency specifically, this article addresses a number of recommendations from the research undertaken with individuals with other chronic health conditions and learning disability. The research suggests that for individuals with learning disabilities autonomy and independence needs to be acknowledged despite their perceived need for increased input from parents and medical professionals. Instead, medical professionals could prioritise their relationship with the adolescent patient by ensuring communication needs are met and that a sense of continuity between paediatric and adult services is maintained. Families can be supported through psychological interventions which provide skills to allow family members to empower their young adult with a learning disability. Specific tools to help the transition process run more smoothly are also recommended and have proven to be effective in other parts of the world.